(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3gdG ShGfG GqOQCJe jGHfj dLC TGA jbGQH Ch hMTG Hg ZQQ s
(3BNQgG (B:s
(3aHjfeG gh jSjQ aj Lha Gddjd EP gh HQLd jMed GHfI UZjQI cCfgG GdHOQ dJeg aCYLHJg hKdGKI CaQGS aaYd Pdc, ced GdLRA GdSGOS ef cJGH GdCZGfj GdLGeY GdcHjQ s
(3ef fSNI NGeSIs
(3hYdjg JbjjOGJs
(3hQO CjVkG JMJ Qbe (B2176s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B43 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B129s
Keywords: (3GdCOHs